e-Business: Roadmap for success - Ravi Kalakota; Marcia Robinson (USA Addison Wesley Longman, Inc., 1999)
Surveys how some successful companies have redesigned their structure and practices to do business on the Internet, and glean from them fundamental design principles for building an electronic business blueprint.
Donated by: Anvar Hodjaev
Keywords: E-business